MULTICULTURAL LITERATURE: THE IDENTITY CONSTRUCTION IN INDONESIAN NOVELS - Akhmad Taufiq (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2014)
This paper examines multicultural literature as a significant and strategic object of study in response to solving national problems. In this context, multicultural literature focuses mainly on multicultural problems frequently found in literary works. One of the main issues is concerned with identity. This article examines Indonesian novels, focusing mainly on the issues of identity: (1) identity and identity problems; (2) identity articulation; (3) text representation on identity discourse in Indonesian novels. The literature sociological approach was adopted to comprehend the reality in multicultural literary texts in Indonesian novels and its relation with the phenomena of identity problems in other field of studies. The results of study indicate that the process of identity articulation and text representation on identity discourse in multicultural social phenomena deserve more serious attention. Furthermore, the problems of identity and the process of identity articulation in multicultural society also require serious attention since identity problems are closely associated with nationality. National identity is not stable but dynamic in dealing with the development of a nation. The lack of concerns on this issue may cause a serious problem of national integrity.